Zonasi kawasan perkotaan berbasis mitigasi bencana banjir (Studi kasus Kota Denpasar) - Irmayanti, Ninda; Lanya, Indayati; Utami, Ni Wayan Febriana (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020DO - 10.24843/JAL.2020.v06.i02.p06, 2020)
Urban zoning based of flood disaster mitigation (case study in Denpasar City). Denpasar City has been experienced a calamitous event such as flooding or inundating caused by development activities and topographical conditions of urban areas which prone to risk to flood disasters. Therefore, urban planning inDenpasar City needs to be handled by developing the concept of flood mitigation approach by considering the level of risk and the characteristics of the city of Denpasar. The purpose of this research was to developzoning concept in urban areas based on flood mitigation approach. The method used in this study wasoverlaying analysis and descriptive analysis. The results showed that the level of flood vulnerability in Denpasar city was increased from 59.62% in 2015 and reached to 61.24% in 2016. The trends caused by a high rainfall during 2016 and was influenced by the hydrogeological characteristics, slope and land use change. Based on spatial analysis, the concept of flooding mitigation formed as follows: 1) high hazard zone(refers to the concept of disaster mitigation in a high hazard area); 2) Medium hazard zone (referring to the concept of disaster mitigation in medium hazard area); 3) Low hazard zone (referring to the concept ofdisaster mitigation in low hazard area). In conclusion it recommended that the government and thecommunity need to work together while maintaining the environment and monitoring the use of space in the urban area. Further research is needed related to hydraulic conditions so that results are more valid.